1999
DOI: 10.1289/ehp.99107s3509
|View full text |Cite
|
Sign up to set email alerts
|

An approach to management of critical indoor air problems in school buildings.

Abstract: This study was conducted in a school center that had been the focus of intense public concern over 2 years because of suspected mold and health problems. Because several attempts to find solutions to the problem within the community were not satisfactory, outside specialists were needed for support in solving the problem. The study group consisted of experts in civil engineering, indoor mycology, and epidemiology. The studies were conducted in close cooperation with the city administration. Structures at risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 8 publications
0
24
0
1
Order By: Relevance
“…Humidity in the CDCCs must be controlled and filtration systems (especially high efficiency filters) should be used to prevent the ingress of mould spores, especially those coming from outdoor sources. Ventilation should also be adequate since poor ventilation together with water leaks cause increased humidity that result in increased fungal growth (Haverinen et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Humidity in the CDCCs must be controlled and filtration systems (especially high efficiency filters) should be used to prevent the ingress of mould spores, especially those coming from outdoor sources. Ventilation should also be adequate since poor ventilation together with water leaks cause increased humidity that result in increased fungal growth (Haverinen et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies also found a higher risk of respiratory symptoms in pupils attending dampness-affected schools (Borr as- Santos et al, 2013;Cai et al, 2011;Haverinen et al, 1999;Jacobs et al, 2014;Meklin et al, 2002;Rylander et al, 1998;Sahakian et al, 2008;Smedje et al, 1997;Simoni et al, 2011;Zhao et al, 2008). The school environment differs from that of the home in several aspects such as size, design, construction materials, ventilation, occupant density, and activities.…”
Section: Introductionmentioning
confidence: 99%
“…Various health problems, including respiratory symptoms and diseases, are known to be associated with microbially contaminated indoor air and can arise, for example, through inhalation of airborne fungal spores. Molds produce a range of mycotoxins (fungal secondary metabolites), some of which are among the most potent (e.g., toxic and carcinogenic) substances known (Haverinen et al, 1999;Morey, 1999;Zureik et al, 2002). Among the suspected causative bacterial agents are the endotoxins (lipopolysaccharides, LPS), which constitute part of the outer membrane of Gram-negative bacteria.…”
Section: Introductionmentioning
confidence: 99%